The Effect of the Discussion Part of the Peer Instruction on the Students' Learning Levels of Turkish Languages (Kazakhstan Sample) - yucel, DOGAN; Kaymak, Burcu (Journal of Research in Turkic Languages, 2022)
The peer instruction method has become an effective learning strategy at all educational levels. The peer instruction method developed by Mazur can be defined as a method in which participants actively participate in the educational process by discussing and helping each other in a peer group during the lesson. In the research, the subjects named “Communication and Media, Technological Developments” in the Harmoni 2 textbook were discussed. In this study, the effect of discussion on the answers of 24 8th-grade students in peer instruction techniques during the lesson was investigated. The application was carried out in Astana City Girls High School (BIL) in Kazakhstan in five weeks with 24 students who took Turkish lessons from Kazakh cognate students whose mother tongue was not Turkish. The data of 50 multiple choice concept test questions asked to the students in the course were analyzed. Data were analyzed using the independent t-test (p=.000) in the SPSS 21.0 program. Considering the results, it was observed that the discussion had an important effect on the transformation of the wrong answers given by the students to the concept test questions into correct answers. Akran öğretimi öğretim yöntemi, tüm eğitim kademelerinde etkili bir öğrenme stratejisi haline gelmiştir. Mazur tarafından geliştirilen akran öğretimi yöntemi, katılımcıların ders sırasında bir akran grubu içinde tartışarak ve grup içinde birbirlerine yardım ederek eğitim sürecine aktif olarak katıldıkları bir metod olarak tanımlanabilir. Araştırmada Harmoni 2 ders kitabındaki “İletişim ve Medya, Teknolojik Gelişmeler” adlı konular ele alınmıştır. 8. sınıfta öğrenim gören 24 öğrencinin ders sırasındaki akran öğretimi tekniklerinde tartışmanın öğrencilerin cevapları üzerindeki etkisi bu çalışmada araştırılmıştır. Uygulama, Kazakistan'daki Astana şehri Kız Lisesinde (BİL) Anadili Türkçe olmayan Kazakistanlı soydaş öğrencilere Türkçe dersinde yer alan 24 öğrenci ile beş haftada gerçekleştirilmiştir. Derste öğrencilere sorulan 50 çoktan seçmeli kavram testi sorularının verileri analiz edilmiştir. Veriler SPSS 21.0 programında bağımsız t-testi (p=.000) kullanarak analiz edilmiştir. Sonuçlara bakıldığında öğrencilerin kavram testi sorularına verdikleri yanlış cevapların doğru cevaplara dönüşmesinde tartışmanın önemli bir etkiye sahip olduğu gözlemlenmiştir.